Quality of work life and workers wellbeing: the industrial social workers approach (2013)
"The aim of this study is to look at quality of work life (QWL) and workers wellbeing through an industrial social workers approach. 264 employees randomly selected from confectionary organizations participated in this study. Five variables to measure QWL: (job satisfaction (JS), capacity development (CD), work and non-work .life balance (WLB), emotional supervisory support (ESS), organizational support (OS), were used to measure health and wellbeing of employees in the workplace. The test indicated the joint effect of the independent variables contributed significantly to the wellbeing of employees (F5, 245=49.039, p<0.05). Using the multiple linear regression, each of the five independent variables are significantly related to workers wellbeing in the following descending order: job satisfaction (t=7.271, β=375), capacity development (t=6.26, p=.269), work and non-work life balance (t=4.108, (3=.214), organizational support (t=3.986, β =.201) and emotional supervisory support (t=2.655, β=.136). It was recommended that a proper understanding of the construct of QWL and the dynamic nature will enable human resource practitioners and industrial social workers take proactive steps in integrating relevant strategies, policies, training programs, procedures and coping strategies to improve the quality of work life of employees so as to guarantee their wellbeing. "